Transient evoked and distortion product otoacoustic emissions in a group of neonates - Silva, Giovanna Cesar [UNESP]; Delecrode, Camila Ribas [UNESP]; Kemp, Adriana Tahara [UNESP]; Martins, Fabiana [UNESP]; Cardoso, Ana Claudia Vieira [UNESP] (Fundação Otorrinolaringologia, 2015)
Introduction The most commonly used method in neonatal hearing screening programs is transient evoked otoacoustic emissions in the first stage of the process. There are few studies comparing transient evoked otoacoustic emissions with distortion product, but some authors have investigated the issue. Objective To correlate the results of transient evoked and distortion product otoacoustic emissions in a Brazilian maternity hospital. Methods This is a cross-sectional, comparative, and prospective study. The study included 579 newborns, ranging from 6 to 54 days of age, born in a low-risk maternity hospital and assessed for hearing loss. All neonates underwent hearing screening by transient evoked and distortion product otoacoustic emissions. The results were analyzed using the Spearman correlation test to relate the two procedures. Results The pass index on transient evoked otoacoustic emissions was 95% and on distortion product otoacoustic emissions was 91%. The comparison of the two procedures showed that 91% of neonates passed on both procedures, 4.5% passed only on transient evoked otoacoustic emissions, 0.5% passed only on distortion product otoacoustic emissions, and 4% failed on both procedures. The inferential analysis showed a significant strong positive relationship between the two procedures. Conclusion The failure rate was higher in distortion product otoacoustic emissions when compared with transient evoked; however, there was correlation between the results of the procedures.
Keywords: Audiology; Neonatal screening; Hearing tests